2012
DOI: 10.3892/ol.2012.1084
|View full text |Cite
|
Sign up to set email alerts
|

Embelin-induced MCF-7 breast cancer cell apoptosis and blockade of MCF-7 cells in the G2/M phase via the mitochondrial pathway

Abstract: Embelin is a small molecular inhibitor extracted from Myrsinaceae plants that specifically inhibits XIAP, affecting the proliferation and apoptosis of various types of tumor cells. In our previous studies, we have demonstrated that embelin is able to induce the apoptosis of MCF-7 breast cancer cells in a dose-dependent manner. However, its mechanism of action is not yet clear. The purpose of this study was to investigate the involvement of the mitochondrial pathway in embelin-induced apoptosis and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Bcl-2). Bcl-2 family members are capable of forming homo and heterodimers with one another suggesting that the overall ratio of pro to anti-apoptoti regulators may determine whether a cell is condemned to die of apoptosis or not (Li et al, 2013). Extensive research into the molecular mechanisms of the apoptotic stimulus has uncovered the Bcl-2 protein family that is thought to function as apoptosis regulators (Ma et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Bcl-2). Bcl-2 family members are capable of forming homo and heterodimers with one another suggesting that the overall ratio of pro to anti-apoptoti regulators may determine whether a cell is condemned to die of apoptosis or not (Li et al, 2013). Extensive research into the molecular mechanisms of the apoptotic stimulus has uncovered the Bcl-2 protein family that is thought to function as apoptosis regulators (Ma et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] (Sigma-Aldrich, Shanghai, China) assay was carried out as described previously (Li et al, 2013). In brief, MDA-MB-231 or MCF 10A cells were seeded at a density of 2.0×10 4 cells/well in 96-well culture plates.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…It has been demonstrated that EB possesses antioxidative [103], antidiabetic [103,104], antianalgesic [105,106], anti-inflammatory [105,106], anticonvulsive [107], wound-healing [108], colitis-protective [109] and hepatoprotective activities [110]. EB also demonstrates antitumor activity in various tumor cells [105,111114], including those of breast [111], colon [112], prostate [113] and pancreas [114]. One major mechanism involves the inhibition of the activity of X-linked inhibitor of apoptosis protein (XIAP) [115].…”
Section: Dual-function Micellar Systemmentioning
confidence: 99%
“…XIAP has been found to be overexpressed in various types of cancers [116], particularly drug-resistant cancers, and XIAP is a promising molecular target for the treatment of cancers [117]. In addition to blocking XIAP activity, EB could inhibit tumor cell growth and induces apoptosis through the suppression of Akt/mTOR/S6K1 [118] and STAT3 signaling cascades [119], downregulation of anti-apoptotic (Bcl-2, Bcl-xL, survivin, IAP-1/2, TNF-α) [111,120] and pro-proliferative (cyclin D1) proteins [112], activation of caspase-3/9 [111,115,121], cleavage of PARP [112], and inhibition of NF-κB activation [122124]. EB has been reported to have a minimal effect on normal prostate epithelial and fibroblast cells with low levels of XIAP [115].…”
Section: Dual-function Micellar Systemmentioning
confidence: 99%